Investigating public financial accounts and coding system in Malawi and measuring agricultural expenditures within the system - Mwabutwa, Chance (International Food Policy Research Institute, 2015)
This paper is one of the four diagnostic studies initiated to better understand the black box of public expenditure statistics and how it varies across countries. Particularly, this paper analyzes how government expenditures in agriculture are captured in Malawi’s public financial accounts. It is anticipated that by providing a clear exposition of the manner in which public agriculture expenditures are identified and aggregated using the existing coding structure, this paper would facilitate easy understanding of the levels and composition of the public agricultural expenditures. Such an understanding would ultimately be necessary for determining the link between such allocations and their impact on agricultural growth and hence economic growth. The report starts with a brief background on reforms in the public financial accounts starting with the adoption of the structural adjustment in the 1980s. This is followed by an analysis of the budget and expenditure classification and coding system and a description of the public agriculture expenditure in Malawi. The consolidation and aggregation of data are based on the administrative, program, economic, and functional classification. One of the main findings show that overtime reforms to classification and coding system ensured compliance to international standards as provided in the 2001 Government Finance Statistics of International Monetary Fund and better linkages of expenditure items to the Malawi Growth and Development Strategy.